Impact of Religion on the Social Status of Women in India: Historical and Legal Overview (Law and Safety, 2025)
The article is devoted to a retrospective study of the impact of religion on the social status of women in India. In particular, it is shown that throughout the long history of Indian civilisation, religion has shaped and changed the idea of women, their place and role in society. In the myths and legends of the prehistoric period, a woman is a divine creation given to a man for a life together. With the penetration of the Aryans deep into Hindustan and the development of Brahmanism, the attitude towards women changed, and their dependence on men increased. The article analyses the main postulates of the Brahminical doctrine, which defined the main purpose of a woman – to give birth. In this sense, the wife was seen as a “field” whose “owner” is the husband. It is shown that the canons of Brahmanism required women to be devoted to their husbands even after his death. This was reflected in the shameful, humiliating attitude towards widows and the tradition of self-immolation of widows, which testified to the wife’s complete dependence on her husband, even after his death. The article examines the religious and philosophical teachings of Jainism and Buddhism, which became a real challenge to Brahmanism, as they broke the established views on the meaning of life, as well as on the place and role of women in the family and society. The original sources are studied, on the basis of which it is concluded that the founders of the new religious and philosophical teachings of that time – Mahavira and Buddha – were not social reformers, since they did not oppose the varna-caste system of society, did not defend the equality of rights of men and women in the modern sense. Nevertheless, they made a significant contribution to solving the gender problems of the society of that time, as Jainism and Buddhism became religions that disregarded the ethnicity and caste of their adherents. The new religions opened up access to spiritual self-realisation and education for women, which was undoubtedly revolutionary. The religious and philosophical teachings of Jainism and Buddhism provoked a negative reaction from Brahmanism. It manifested itself in an even stricter canonical consolidation of the hierarchy of varna, ranking of marriage forms and rules of behaviour in the family. Subsequently, Hinduism, which became the dominant religion in India, effectively deprived women of their rights and established the complete supremacy of male power in society and in the family.
Keywords: India; dharma; woman; family; Buddhism; Jainism; Hinduism; sati.